The potential of a digital, transdisciplinary approach to landscape change and urbanization around Copenhagen in the 20th century. Issue 1 (2nd January 2019) - Svenningsen, Stig; Perner, Mads Linnet
ABSTRACT: Urbanization has long been recognized as a major driver for landscape change in the vicinity of major cities and urban systems. Studies of the historical process of urbanization often rely on spatial data or statistics and rarely include detailed historical socio-economic data. This research note aims to emphasize the potential of using digitized cultural heritage data in landscape research. The focus is on how a digital transdisciplinary approach, combining an array of large historical data sets, can provide insights into the link between socio-economic factors and landscape changes at the property level. Using the case of a single farm on the outskirts of Copenhagen, we demonstrate how linked historical data can help reconstruct the urbanization process on a local scale and trace the driving forces of landscape change. The results also suggest that there is enormous potential for landscape research to utilize such historical data.